Serine/threonine phosphatase 5 (PP5C/PPP5C) regulates the ISOC channel through a PP5C-FKBP51 axis. (February 2018) - Hamilton, Caleb L.; Abney, Kevin A.; Vasauskas, Audrey A.; Alexeyev, Mikhail; Ni, Li; Honkanen, Richard E.; Scammell, Jonathan G.; Cioffi, Donna L.
Pulmonary endothelial cells express a store-operated calcium entry current ( I soc ), which contributes to inter-endothelial cell gap formation. I soc is regulated by a heterocomplex of proteins that includes the immunophilin FKBP51. FKBP51 inhibits I soc by mechanisms that are not fully understood. In pulmonary artery endothelial cells (PAECs) we have shown that FKBP51 increases microtubule polymerization, an event that is critical for I soc inhibition by FKBP51. In neurons, FKBP51 promotes microtubule stability through facilitation of tau dephosphorylation. However, FKBP51 does not possess phosphatase activity. Protein phosphatase 5 (PP5C/PPP5C) can dephosphorylate tau, and similar to FKBP51, PP5C possesses tetratricopeptide repeats (TPR) that mediate interaction with heat shock protein-90 (HSP90) chaperone/scaffolding complexes. We therefore tested whether PP5C contributes to FKBP51-mediated inhibition of I soc . Both siRNA-mediated suppression of PP5C expression in PAECs and genetic disruption of PP5C in HEK293 cells attenuate FKBP51-mediated inhibition of I soc . Reintroduction of catalytically competent, but not catalytically inactive PP5C, restored FKBP51-mediated inhibition of I soc . PAEC cell fractionation studies identified both PP5C and the ISOC heterocomplex in the same membrane fractions. Further, PP5C co-precipitates with TRPC4, an essential subunit of ISOC channel. Finally, to determine if PP5C is required for FKBP51-mediated inhibition of calcium entry-induced inter-endothelial cell gap formation, we measured gap area by wide-field microscopy and performed biotin gap quantification assay and electric cell-substrate impedance sensing (ECIS®). Collectively, the data presented indicate that suppression of PP5C expression negates the protective effect of FKBP51. These observations identify PP5C as a novel member of the ISOC heterocomplex that is required for FKBP51-mediated inhibition of I soc .